2015
DOI: 10.1093/mnras/stv1514
|View full text |Cite
|
Sign up to set email alerts
|

The RMS survey: ammonia mapping of the environment of massive young stellar objects

Abstract: We present the results of ammonia observations towards 66 massive star forming regions identified by the Red MSX source survey. We have used the Green Bank Telescope and the K-band focal plane array to map the ammonia (NH 3 ) (1,1) and (2,2) inversion emission at a resolution of 30 ′′ in 8 ′ regions towards the positions of embedded massive star formation. We have identified a total of 115 distinct clumps, approximately two-thirds of which are associated with an embedded massive young stellar object or compact… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
34
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 76 publications
(93 reference statements)
8
34
0
1
Order By: Relevance
“…(Wang et al 2009), but is lower than that found with NH 3 (Wouterloot et al 1988;Myers et al 1991;Jijina et al 1999;Wu et al 2006;Urquhart et al 2011Urquhart et al , 2015. The correlation appears consistent with the idea that the internal velocity dispersion of the dense clumps can be used to determine the mass of the formed stars (Saito et al 2001).…”
Section: Line Width-luminosity Relationsupporting
confidence: 80%
See 3 more Smart Citations
“…(Wang et al 2009), but is lower than that found with NH 3 (Wouterloot et al 1988;Myers et al 1991;Jijina et al 1999;Wu et al 2006;Urquhart et al 2011Urquhart et al , 2015. The correlation appears consistent with the idea that the internal velocity dispersion of the dense clumps can be used to determine the mass of the formed stars (Saito et al 2001).…”
Section: Line Width-luminosity Relationsupporting
confidence: 80%
“…Previous observations of NH 3 (Wouterloot et al 1988;Myers et al 1991;Harju et al 1993;Ladd et al 1994;Molinari et al 1996;Jijina et al 1999;Wu et al 2006;Urquhart et al 2011Urquhart et al , 2015, C 18 O (Saito et al 2001;Ridge et al 2003;Maud et al 2015), and 13 CO (Wang et al 2009;Lundquist et al 2015) suggest that the line width is correlated with luminosity, which indicates the presence of a link between formed stars and velocity dispersion. We investigate the line width-luminosity relation in the case of the dense gas tracer H 2 CO. We plot the line width-luminosity relation in Figure 9.…”
Section: Line Width-luminosity Relationmentioning
confidence: 90%
See 2 more Smart Citations
“…Pillai et al 2006;Longmore et al 2007;Hill et al 2010;Ragan, Bergin & Wilner 2011;Dunham et al 2011;Urquhart et al 2011;Wienen et al 2012;Urquhart et al 2015).…”
Section: H a R Ac T E R I Z I N G T H E P Ro P E Rt I E S O F H O Punclassified